Une ethnographie des appropriations touristiques d’une croisière maritime en Chine - Véronique Mondou; Benjamin Taunay (Mondes du Tourisme, 2016)
In a context of strong tourism growth in China (PRC), the potential of this country has not been invisible to the international cruise companies seeking new growth markets. The Chinese central government is at the same time giving cruising activity pride of place in its tourism development projects. The activity of cruising is therefore operating under favorable conditions, jointly encouraged by public bodies and the US multinationals. But there is another factor to consider in order to understand the nature of the phenomenon: Chinese cruise passengers. From a highly restricted activity just 6 years ago it has become, in the opinion of the cruise companies, travel agencies and Chinese tour operators, a hugely promising tourism segment. If Chinese tourists are attracted by the idea of cruising, we can question their expectations with regard to this product of American culture. Without any will of generalization, and from an exploratory “in situ” observation period, we need to compare the observed behavior with the previously acquired knowledge. The work presented here therefore focuses on providing ways to understand the phenomenon of cruising adopted by Chinese tourists.